Induction chemotherapy with carboplatin, nab-paclitaxel and cetuximab for at least N2b nodal status or surgically unresectable squamous cell carcinoma of the head and neck. (September 2018) - Weiss, Jared; Gilbert, Jill; Deal, Allison Mary; Weissler, Mark; Hilliard, Chris; Chera, Bhishamjit; Murphy, Barbara; Hackman, Trevor; Liao, Jay Justin; Grilley Olson, Juneko; Hayes, David Neil
Abstract: Background: Although induction studies of TPF in SCCHN have not improved outcomes compared to chemoradiotherapy alone, phase II studies of weekly carboplatin (CbP), paclitaxel and cetuximab (C225) have shown promising results. Nano-albumin-paclitaxel (nab-paclitaxel) based chemotherapy has demonstrated a higher response rate (RR) than solvent-based paclitaxel in squamous cell carcinoma of the lung with favorable toxicity. Materials and methods: Patients with treatment naïve SCCHN of any site with ≥N2b disease or that was unresectable by strict criteria were eligible. Patients were treated with nab-paclitaxel 100 mg/m 2, CbP area under the curve (AUC) 2 and C225 400 mg/m 2 week 1 then 250 mg/m 2 for six weeks, followed by standard of care chemoradiotherapy (CRT). The primary endpoint was clinical response rate to induction therapy as defined by RECIST version 1.1. Secondary measures included toxicity, progression-free survival, overall survival and quality of life as measured by FACT-HN. Results: 38 eligible subjects were treated. Primary sites were: oropharynx (OPX) (25), larynx (3) oral cavity (OC) (9), hypopharynx (1). The most common grade 3 or 4 toxicity during induction was acneiform rash (26%) followed by neutropenia (16%). RR was 76.3%. Median PFS and OS have not been reached (median follow-up of 3.3 years); they were superior in patients with response. Conclusions: The combination of nab-paclitaxel, CbP and C225 is feasible, tolerable and active against locally advanced SCCHN.